2015
DOI: 10.18063/ijps.2015.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Concordance and discordance between objectively and subjectively measured successful aging and their linkages with mortality

Abstract: Successful aging has extended from the biomedical-oriented model to the biomedical-and-psychosocial mixed model. However, few studies have investigated the subtypes of the joint classification between subjective (psychosocial-oriented) (SSA) and objective (biomedical-oriented) (OSA) measures to identify and distinguish different risk groups. This study aims to examine how concordance and discordance between SSA and OSA are associated with sub-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…This focus on objective measurements has, however, been the main critique of the concept with commentators and researchers arguing it fails to consider individuals' own views of what makes ageing successful (Martinson & Berridge, 2015). For example, Gu's (2015) analysis of older adults in the Chinese Longitudinal Healthy Longevity Survey found that objective measures of successful ageing (absence of chronic disease and no functional disability of cognitive impairment) do not always correspond with subjective measures (life satisfaction, self-reported health, and distress). Indeed, there was discordance between objective and subjective measures among 23% of women and 29% of men.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This focus on objective measurements has, however, been the main critique of the concept with commentators and researchers arguing it fails to consider individuals' own views of what makes ageing successful (Martinson & Berridge, 2015). For example, Gu's (2015) analysis of older adults in the Chinese Longitudinal Healthy Longevity Survey found that objective measures of successful ageing (absence of chronic disease and no functional disability of cognitive impairment) do not always correspond with subjective measures (life satisfaction, self-reported health, and distress). Indeed, there was discordance between objective and subjective measures among 23% of women and 29% of men.…”
Section: Literature Reviewmentioning
confidence: 99%
“…SA models as predictors of mortality have been tested and have shown significant results [21]. However, the existing literature does not indicate whether biomedical and psychosocial SA predicts mortality differently according to SES.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the use of healthy aging concepts that include both components with a biomedical focus and components with a psychosocial focus enhances the promotion of a holistic consideration of the aging process. This has been suggested as important for the development of “people‐centered” prevention strategies, as both dimensions are crucial for the well‐being of aging individuals .…”
Section: Introductionmentioning
confidence: 99%